2016
DOI: 10.1093/infdis/jiw199
|View full text |Cite
|
Sign up to set email alerts
|

Broad and Temperature Independent Replication Potential of Filoviruses on Cells Derived From Old and New World Bat Species

Abstract: Filoviruses are strongly associated with several species of bats as their natural reservoirs. In this study, we determined the replication potential of all filovirus species: Marburg marburgvirus, Taï Forest ebolavirus, Reston ebolavirus, Sudan ebolavirus, Zaire ebolavirus, and Bundibugyo ebolavirus. Filovirus replication was supported by all cell lines derived from 6 Old and New World bat species: the hammer-headed fruit bat, Buettikofer's epauletted fruit bat, the Egyptian fruit bat, the Jamaican fruit bat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…However, sampling bone marrow from M. myotis requires sacrificing a wild animal and therefore this study was limited to one individual euthanized due to an opportunistic event. This is typical of studies employing cell lines derived from wild bat species (Kuhl et al, 2011 ;Miller et al, 2016). Myotis myotis macrophages, of size and shape indistinguishable compared to their murine analogues, were successfully differentiated in medium containing mouse M-CSF, and were responsive to widely used TLR ligands, LPS and Poly(I:C) (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…However, sampling bone marrow from M. myotis requires sacrificing a wild animal and therefore this study was limited to one individual euthanized due to an opportunistic event. This is typical of studies employing cell lines derived from wild bat species (Kuhl et al, 2011 ;Miller et al, 2016). Myotis myotis macrophages, of size and shape indistinguishable compared to their murine analogues, were successfully differentiated in medium containing mouse M-CSF, and were responsive to widely used TLR ligands, LPS and Poly(I:C) (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…These hypotheses still largely lack functional confirmation, particularly with RNA virus infection. A recent study demonstrated a temperature-independent replication of Filoviruses on bat cells, as opposed to the 'flight as fever' hypothesis 57 . We demonstrate here a dampened NLRP3mediated inflammatory response to three different types of RNA virus in bat immune cells, with no or minimal difference in viral titres.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, Nunes-Correia et al (1999) reported that the binding affinity of AIV H1N1 to canine kidney cells increased by over 10-fold from 4°C to 37°C. In the case of filovirus infectivity, Miller et al (2016) demonstrated that at 72 h, titres of Ebola virus Makona and Marburg virus Angola were 1000-fold and 100-fold higher, respectively, at 41°C than at 37°C in Rousettus aegyptiacus cell lines (although they were both similar at the 96 h end point). This is not consistent with a negative ΔH a_receptor for GP binding to Cr and indeed suggests a positive ΔH a_receptor as in entropy-driven binding (Fig.…”
Section: To Identify Mechanisms By Which the Effect Of Temperature Onmentioning
confidence: 99%